Scaff Folding based Problem- Solving Activity in Analog Communication - Unissa, Azeem; ., Ashmitha; ., Sanchita (Journal of Engineering Education Transformations, 2018)
Problem-Based Learning (PBL) holds the promise of training students to tackle unclear, ill-structured problems and enhance transference of student knowledge from typical classroom activities to real-world design and analysis. The case study was introduced to engineering undergraduates at Central State University, US. The proposed method uses gamification is one of the techniques for implementation to motivate students to participate in the process of learning. By constantly increasing the system complexity, students strengthen their conceptual understanding, mathematical kills as well as problem- solving expertise In previous studies, it has been observed that in most of the engineering courses students face difficulties in solving methodical problems due to lack of theoretical understanding and basic knowledge while solving engineering problems. Problem solving skills are one of the higher-order intellectual skills need to be inculcated to all the twenty-first-century learners. Additionally, professors often assume that problem- solving ability increases by mastering a specific field conceptualization as well as mastering relevant problem solving by encouraging students. At (institution name) in the course EMTL, AC, PTSP, other courses students face difficulties in understanding problem statement and also solve the problems properly. In order to infix the problem solving skills, this research is carried out which uses gamification and scaffolding concept.